2020
DOI: 10.1002/jca.21798
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the use of therapeutic plasma exchange in multiple myeloma

Abstract: Introduction Therapeutic plasma exchange (TPE) is traditionally performed for hyperviscosity, neuropathy and to mitigate renal injury in the setting of high clonal free light chain burden in patients with multiple myeloma (MM) with unknown clinical benefit. Materials and Methods Retrospective study of adults ≥18 years with MM who received TPE in the in‐patient setting in the United States from 1993 to 2015. We examined the temporal trends of TPE utilization in MM hospitalizations, hospital charges, in‐hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The first day of hospitalization was related to the remission of the patient’s condition and the economic expenses of hospitalization. The median FLOS in most patients was 10 days (IQR 6.8–17.6 days), which is consistent with Dhakal et al.’s reported hospital stay of 11.9 days (IQR 7.2–17.6 days) under TPE treatment [ 50 ]. The median FLOS of patients with severe infection, rheumatic immune disease, severe organ failure, etc., was significantly prolonged (22.0 days).…”
Section: Discussionsupporting
confidence: 86%
“…The first day of hospitalization was related to the remission of the patient’s condition and the economic expenses of hospitalization. The median FLOS in most patients was 10 days (IQR 6.8–17.6 days), which is consistent with Dhakal et al.’s reported hospital stay of 11.9 days (IQR 7.2–17.6 days) under TPE treatment [ 50 ]. The median FLOS of patients with severe infection, rheumatic immune disease, severe organ failure, etc., was significantly prolonged (22.0 days).…”
Section: Discussionsupporting
confidence: 86%
“…Nineteen US and 14 non-US studies reported on sex and survival (Supplementary Table 10 ), and six US and 10 non-US studies on sex and mortality (Supplementary Table 11 ). Most studies reported no effect of sex on survival or mortality [ 16 , 25 , 27 , 32 , 34 , 38 , 45 , 56 , 59 , 63 , 66 , 68 , 69 , 74 , 75 , 80 , 84 , 90 , 92 , 97 ]. However, a subset of studies reported more favorable survival in women [ 14 , 22 , 29 , 40 , 41 , 43 , 48 , 55 , 61 ], and mortality rates were generally higher in men [ 29 , 44 , 46 , 67 , 70 , 77 , 82 , 89 , 92 , 94 , 98 , 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the lack of solid supportive data supporting its role in MC-AKI, its use reportedly increased over the past two decades. 12 A disadvantage of TPE is the indiscriminate removal of most plasma proteins, which renders it less efficient and can contribute to complications because of the loss of essential proteins (e.g., clotting factors). Thus, a strategy that more selectively removes proteins in the FLC size range (22.5-45 kD) was devised by performing hemodialysis (HD) using HCO-HD filters, which have molecular mass cutoffs of 45-60 kD.…”
Section: Effectiveness Of Extracorporeal Flc Removal On Mm-akimentioning
confidence: 99%
“…Despite the lack of solid supportive data supporting its role in MC-AKI, its use reportedly increased over the past two decades. 12 …”
Section: Effectiveness Of Extracorporeal Flc Removal On Mm-akimentioning
confidence: 99%